2015
DOI: 10.1002/jsfa.7205
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic and cloned animals in the food chain – are we prepared to tackle it?

Abstract: Transgenic and cloned animal production for various purposes has been increasing rapidly in recent times. While the actual impact of these animals in the food chain is unknown, the significance of tracking and monitoring measures to curb accidental and or deliberate release has been discussed. Religious perspectives from different faiths and traditions have been presented. Although the concept of substantial equivalence satisfies the technical and nutritional requirements of these products when assessed agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…So, GFs continue to be a topic of controversy and debate all over the world. In fact, several studies document a robust link between GFs and fear (Jagadeesan and Salem, 2015; Ronteltap et al , 2007; Lusk et al , 2006). For instance, some authors found that people’s general neophobia was correlated with their concerns and negativity regarding novel food technologies (Defez, 2016; Wunderlich and Gatto, 2015; Šorgo and Ambrožič-Dolinšek, 2010; Yunta et al , 2005; Pardo et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…So, GFs continue to be a topic of controversy and debate all over the world. In fact, several studies document a robust link between GFs and fear (Jagadeesan and Salem, 2015; Ronteltap et al , 2007; Lusk et al , 2006). For instance, some authors found that people’s general neophobia was correlated with their concerns and negativity regarding novel food technologies (Defez, 2016; Wunderlich and Gatto, 2015; Šorgo and Ambrožič-Dolinšek, 2010; Yunta et al , 2005; Pardo et al , 2002).…”
Section: Introductionmentioning
confidence: 99%